EDUCATIONAL VIDEO AS AN EFFORT TO REDUCE THE INCIDENCE OF POSTPARTUM BLUES AT MUNTILAN HEALTH CENTER - Wulandari, Risky Puji; Meilani, Mita; Abidah, Alief Nur insyiroh; Perwitasari, Perwitasari (Jurnal Smart Kebidanan, 2025)
Background: The postpartum period has a strong position as a risk factor for the development of serious mood disorders that can lead to postpartum blues and even depression. Postpartum blues is one of the adjustment disorders after childbirth in the form of feelings of sadness and anxiety that occur on day 3 to day 5 in the first 14 days after childbirth. This condition can cause bounding attachment problems between mother and baby, delays in physical, social, and cognitive development in infants. In other aspects, it affects postpartum care, maternal health, and greatly affects the mother's quality of life. Methods: This study was a type of quantitative research with a quasy experiment design. Total population of 50 mothers with total sampling, the number of samples of this study was 50 respondents. Observations were made twice, namely before and after the experiment and there was a control and intervention group (25 samples/group). Results: There was a rfesignificant difference in the average postpartum blues (EPDS score) before and after being given an educational video in the intervention group with a p-value of 0.000 (p <0.05). The data normality test used Shapiro Wilk with the results of the normally distributed data with a p value of >0.05. The bivariate test uses the paired t-test, which is to determine the effect  of educational videos as an effort to reduce the incidence of postpartum blues before and after the provision of educational videos in the intervention group and control group. There was a decrease in EPDS scores with a difference between post-test and pre-test of 5.16. Researchers 95% believe that the difference in EPDS scores before the educational video with EPDS scores after education is between 4.53 to 5.80l. Conclusion: Video education is proven to have an effect on reducing the incidence of postpartum blues in the group given educational videos. Respondents in the intervention group experienced a significant decrease in postpartum blues compared to the control group.